Impact of Chronic Inflammation in Psoriasis on Bone Metabolism - Saalbach, Anja; Kunz, Manfred (Frontiers in Immunology, 2022)
Psoriasis is a chronic inflammatory disease of the skin and joints associated with several comorbidities such as arthritis, diabetes mellitus and metabolic syndrome, including obesity, hypertension and dyslipidaemia, Crohn’s disease, uveitis and psychiatric and psychological diseases. Psoriasis has been described as an independent risk factor for cardiovascular diseases and thus patients with psoriasis should be monitored for the development of cardiovascular disease or metabolic syndrome. However, there is mounting evidence that psoriasis also affects the development of osteoporosis, an important metabolic disease with enormous clinical and socioeconomic impact. At present, there are still controversial opinions about the role of psoriasis in osteoporosis. A more in depth analysis of this phenomenon is of great importance for affected patients since, until now, bone metabolism is not routinely examined in psoriatic patients, which might have important long-term consequences for patients and the health system In the present review, we summarize current knowledge on the impact of psoriatic inflammation on bone metabolism and osteoporosis.